Artificial Intelligence and Expert Systems: Its Emerging Interaction and Importance in Information Science – An overview - Prantosh Kr. Paul, C.; Senthamarai, R.; Shivraj, K. S.; Chatterjee, D.; Karn, B. (Asian Journal of Electrical Sciences, 2012)
This paper mainly deals with overview of artificial intelligence and Expert System. Artificial Intelligence primarily responsible for developing computer programs which are able to read, speak, and understand as like man. Other hand Expert System refers to expert System needed for advance decision and intelligence robotics application. Expert System can communicate with user in their natural language and processes the capacity to catch to the individual desire. Here in this paper role of Artificial Intelligence and Expert System elaborate briefly, where as application of these computer techniques get most priority. We also discuss the need of Artificial Intelligence and emerging Expert System in the working and academic field of information Science.